Dyslipidemia and the Risk of Alzheimer’s Disease - Reitz, Christiane (2013)
Whether cholesterol is implicated in the cause of Alzheimer’s disease (AD) is still controversial. Several studies that explored the association between lipids and/or lipid-lowering treatment and AD indicate a harmful effect of dyslipidemia on AD risk. The findings are supported by genetic linkage and association studies that have clearly identified several genes involved in cholesterol metabolism or transport as AD susceptibility genes, including apolipoprotein E (APOE), apolipoprotein J (APOJ, CLU), ATP-binding cassette subfamily A member 7(ABCA7), and sortilin-related receptor (SORL1). Functional cell biology studies further support a critical involvement of lipid raft cholesterol in the modulation of Aβ precursor protein processing by β-secretase and γ-secretase resulting in altered Aβ production. However, conflicting evidence comes from epidemiological studies showing no or controversial association between dyslipidemia and AD risk, randomized clinical trials observing no beneficial effect of statin therapy, and cell biology studies suggesting that there is little exchange between circulating and brain cholesterol, that increased membrane cholesterol level is protective by inhibiting loss of membrane integrity through amyloid cytotoxicity, and that cellular cholesterol inhibits colocalization of β-secretase 1 and Aβ precursor protein in nonraft membrane domains, thereby increasing generation of plasmin, an Aβ-degrading enzyme. The aim of this article is to provide a comprehensive review of the findings of epidemiological, genetic, and cell biology studies aiming to elucidate the role of cholesterol in the cause of AD.